Perlindungan Hukum terhadap Konsumen atas Barang Tiruan Pada Transaksi E-Commerce (Studi Kasus pada Toko Stridewear.Id Bali) - Gde Nanda Radithya Kresnantara Sanjaya; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
In respecting the rights of consumers, complete and accurate information is very important for an item in upholding consumer rights, goods purchased elsewhere which are for resale are not genuine and have been missed from checking for originality in stores. It was found that the goods purchased by consumers in other stores were not authentic and the goods purchased by consumers were missed from checking for originality at the store. In respecting the rights of consumers, it is important that business actors provide information on the accuracy of a service or goods, so that the problem is guided by Law No. 8 of 1999 concerning Consumer Protection. The purpose of this study is to determine the form of consumer protection in e-commerce and to find solutions for the responsibility of business actors to consumers. This study uses an empirical study type using a statutory approach and a conceptual approach. Stridewear.Id in carrying out the form of legal responsibility to consumers, prefers to use civil legal responsibility, namely through compensation actions which can be in the form of the same goods, as well as money, in accordance with the agreement between the consumer and the shop owner or business actor.